2011
DOI: 10.1002/cncy.20130
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of fine‐needle aspiration specimens for future use in RNA‐based molecular testing

Abstract: Background The application of ancillary molecular testing is becoming more important for the diagnosis and classification of disease. The use of fine-needle aspiration (FNA) biopsy as the means of sampling tumors in conjunction with molecular testing could be a powerful combination. FNA is minimally invasive, cost effective, and usually demonstrates accuracy comparable to diagnoses based on excisional biopsies. Quality control (QC) and test validation requirements for development of molecular tests impose a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…However, as the aim of this study was to compare different approaches in parallel for the detection of EGFR mutations from MPE samples, this limitation should not hamper our objective. Moreover, although our study suggested the promise of using RNA for EGFR analysis, the inherently labile nature of RNA, as well as the ubiquitous presence of RNase, warrants careful sample processing in RNA-based molecular testing [46].…”
Section: Lung Cancer T-h Tsai Et Almentioning
confidence: 87%
“…However, as the aim of this study was to compare different approaches in parallel for the detection of EGFR mutations from MPE samples, this limitation should not hamper our objective. Moreover, although our study suggested the promise of using RNA for EGFR analysis, the inherently labile nature of RNA, as well as the ubiquitous presence of RNase, warrants careful sample processing in RNA-based molecular testing [46].…”
Section: Lung Cancer T-h Tsai Et Almentioning
confidence: 87%
“…[57][58][59][60][61][62] A variety of cytology platforms have been validated for mutation testing. 63 Ninety-eight percent of lung cytology samples were suitable for epidermal growth factor receptor and KRAS mutation testing in a recent study.…”
Section: Targeted Therapies Based On Cytologymentioning
confidence: 99%
“…It recently was demonstrated that the cellular morphology and RNA integrity necessary for studies of gene expression are maintained with cryopreserved samples. 15 The detection of phosphorylated signaling proteins in FNAs for the measurement of pathway activity using multiplexed analysis has been described and presents the opportunity for its application in drug response studies and functional assays. 16 New miniaturized devices using different platforms may add useful data to morphological assessment and could be integrated into the clinical routine to improve the speed with which results are determined.…”
Section: Other Alternatives and Novel Specimen Preservation Techniquesmentioning
confidence: 99%